Museum Istiqlal dan Identitas Keislaman di Indonesia - Irmawati Marwoto Johan (SUHUF, 2011)
Based on the concept of the new museology, a museum is seen to function as an educational institution that aims to  increase and strengthen society’s awareness of  its  own  identity so that it will realise the  potenial for better development. Museum Istiqlal is a museum that represents Islamic identity in Indonesia and its goal is for the Museum  to  become a location where  the community  can learn more  about  this subject.    The museum seeks to promote wider  understanding about the variety of social and daily life in Islamic cultures in Indonesia, as well as about  religious harmony,  which is inclusive  Islam, and  also  many other subjects.